DNASe I and structure Catalytic site - Sulviani, Nurul (JURNAL BIOSAINS, 2024)
This Article describes 3Dimention studies carried out of catalytic site  over the past year which have advanced of understanding the substrate to recognizition and how the catalytic mechanism of the several key DNAse I. The hydrolysis reaction that occurs in DNASe I is influenced by Mg 2+ and Ca 2+ but let the Binding of DNASe I ions is still unclear, the active side is found, the amount and mechanism of Ca2+ and Mg2+ . The results of the review in this article indicate that DNASe I is needed externally from experimental animals and simulations improve the binding reaction of Ca 2+ and Mg 2+ which is supported by some literature that uses crystallographic studies where Ca 2+ ions can stabilize DNASe I and also in the presence of Mg 2+ ions that can accelerate the hydrolytic failure of the cation. The results of the review explain the role of cations collectively electrostatic matching between DNASe I and DNA.